KINERJA PANITIA PEMILIHAN KECAMATAN (PPK) DALAM PENYELENGGARAAN PEMILIHAN UMUM ANGGOTA DPR, DPD DAN DPRD TAHUN 2014 DI KECAMATAN PALASA KABUPATEN PARIGI MOUTONG - Haris, Haris (Katalogis, 2016)
This study aims to identify and analyze the performance of sub district election committee (PPK) in the palasa sub district in the parigi moutong district. This type of research uses descriptive qualitative approach, measure performance based on the opinions Dwiyanto et al, (2002: 48-49) consists of: productivity, service quality, responsiveness, responsibility and accountability. The collection of data through observation, interview, and documentation, dianlisis through the stages of data reduction, data display, and conclusion. The study concluded that the performance of the District Election Committee (PPK) District of Palasa, not maximum yield general election (election) in 2014, DPR, DPD and DPRD in District Palasa, based on productivity, service quality, responsiveness, responsibility and accountability. The lack of availability of inputs, especially the time and cost of implementation since socialization until the voting was inadequate. There are still people who have not registered as voters remain, because the task of updating the voter is not maximized executed so that some people use the ID card at the timeo fchoosing.